Modeling Aortic Stenosis progression: impact on follow-up, treatment, and survival - Diana Filipa Costa Ribeiro (2022)
Aims: Aortic stenosis (AS) is a progressive disease of the aortic valve and ultimately of the myocardium, potentially fatal. This study aims to 1) evaluate the rate of AS progression, 2) cluster patients into rapid progressors (RP) and slow progressors (SP) and explore possible predictors, 3) evaluate the impact of different progression rates on cardiac structure and function, and 4) evaluate survival, optimal timing for follow-up and treatment. Methods and results: We retrospectively identified 752 patients with mild to severe AS who had undergone > 1 echocardiogram (9583 studies), from 2012 to 2020. Seriated echocardiograms, biomarkers and clinical records were consulted, providing a multiparametric data frame for modeling AS progression, its determinants, and consequences. AS progression was evaluated by modeling aortic peak velocity as a function of time, fitting a generalized logistic function. 83% of patients were classified as SP and 17% as RP, with acceleration rates estimated in 0.06/year and 0.34/year, respectively (p< 0.001). There was no association between progression rate and clinical variables. Despite no survival difference between these groups, RP registered higher rates of valvular intervention (p <0.001) and earlier cardiac damage, as demonstrated by early onset of tricuspid valve regurgitation, left auricle dilation, and left ventricle hypertrophy (p<0.05). Conclusions: A nonlinear model of AS progression and two clusters of progressors were identified. Despite overlapping baseline characteristics and survival rates, RP displayed earlier cardiac damage and treatment. Therefore, assessment of AS acceleration rate may enhance AS stratification and provide a proactive time frame for follow-up and intervention.